Competency‐based nursing: Reducing cost while maintaining or improving quality. Issue 2 (6th May 2021) - Hossler, Chuck; James, Alton
Abstract: The advent of COVID‐19 and subsequent social disruption has exacerbated existing nursing workforce shortages. As nursing education programs and healthcare providers struggle to meet the care needs of their respective communities, the ever‐present challenge of replenishing nursing candidates persists—particularly when those candidates face financial hardships to complete their education. In an effort to mitigate financial hardships, competency‐based education (CBE) nursing offers the opportunity for students to self‐pace their learning and potentially complete their education more quickly. In addition to CBE programs typically being more affordable that traditional "seat time" credit‐based programs, students can potentially yield even more significant savings. Therefore, considering some healthcare providers, accreditors, and candidates may be concerned with CBE program quality, this study assesses the merit of that assertion. Through a comparative of analysis of Western Governors University's (WGU) CBE Nursing Program to similar traditional education state nursing programs, this research finds that CBE nursing programs can reduce cost while maintaining or even improving program quality by a measure of NCLEX pass rates.